Pilomatricoma in the pinna: a case report - Timna, C. J.; Chandrika, D. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Benign calcifying epithelioma of Malherbe or pilomatricoma is rare benign skin tumours, typically seen in head and neck region. This is supposed to arise from hair follicle matrix cells. Though head and neck is the commonest area involved by this tumour, only 4.5% cases have been reported in the pinna. Neck is most commonly involved followed by cheek, scalp, pre auricular and peri orbital areas. Here we report a case of pilomatricoma over medial surface of pinna in a 20 years old female. She had the swelling which was gradually increasing for the past 5 years. Histopathological examination following excision biopsy confirmed the diagnosis.